STUDENTS’ ABILITY IN CHANGING ACTIVE SENTENCES INTO PASSIVE ONES OF PRESENT PERFECT CONTINUOUS TENSE - Dian Eka Putri (English Language Education and Current Trends (ELECT), 2022)
This research was purposed to describe the second year students’ ability in changing active sentences into passive ones. The research design was descriptive in nature. The population of this research was the second year students at English Department of Bung Hatta University with total population 104 students. The writer used cluster random sampling technique in taking the sample. The result of the data analysis showed that 24 out of 28 students had moderate ability in changing active sentences into passive ones . In detail, the findings showed that 25 out of 28 students  had moderate ability in changing the subject of active sentences into passive ones. 20 students out of 28 students had moderate ability in changing the auxiliary of active sentences into passive ones. 23 out of 28 students had moderate ability in the use of be in changing active sentences into passive ones.  26 out of 28 students had moderate ability in the use of be + ing in changing active sentences into passive ones. 22 out of 28 students had moderate ability in changing the verb of active sentences into passive ones. 27 out of 28 students had moderate abilityin the use of agent in changing active sentences into passive ones. The last,  24 out of 28 students had moderate ability in the use of time signal in changing active sentences into passive ones.   REFERENCES  Allsop, J. 1990. Cassel’s Students English Grammar. Jakarta Barat: Indonesia Alter, J. B. 1993. Essential English Usage and Grammar 5. Jakarta: Binarupa Aksara. Arikunto, Suharsimi. 2012. Dasar-dasar Evaluasi Pendidikan (Edisi Revisi). Jakarta: Binarupa Aksara. Azar, B. S. 1993. Fundamentals of English Grammar (2nd ed). Jakarta: Binarupa Aksara. Eastwood, J. 2002. Oxford Guide to English Grammar. Oxford: Oxford University press. Fuchs, M. Bonner, M. and Westheimer, M. 2000. Focus on Grammar (2nd ed). London: Addison Wesley Longman, Inc. Gay. L. R. 1987. Educatinal Research: Competencies for Analysis and Application (3rd ed). Ohio: Merrill Publishing Company. Murphy, R. 2002. English Grammar in Use, With Answers-Intermediate (2nd ed). Jakarta: Penerbit Erlangga. Murphy, R. 1989. English Grammar in Use (6th ed). Cambridge: Cambridge University Press. Nordquist. R. 2013. Tense. http://grammar.about.com/od/tz/g/tenseterm.htm (accessed on December 28th, 2013). Webster. M. 2013. Tense.http://www.merriam-webster.com/dictionary/tense (Accessed on December 28th, 2013). Werner, P. K. et. al. 2002. Interaction 2 grammar (4th ed). New York: McGraw-Hill/Contemporary. Woods, E. And Mcleod, N. 1992. Using Basic English Grammar. London: Prentice Hall International